Community Empowerment Strategy in Tourism Village Development in Bandung Regency - Helmi Andriansah; Thomas Bustomi; Soleh Suryadi (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2026)
This study aims to analyze the condition of community empowerment, the inhibiting factors, and the empowerment strategies in the development of Alamendah Tourism Village in Bandung Regency. The study employed a qualitative approach with a case study design through in-depth interviews, field observations, and document analysis. The results indicate that community empowerment is still in a transitional stage. Although several positive dynamics have emerged, such as the initial establishment of relationships between managers and the community, community involvement in several activities, and efforts in documentation and promotion, the empowerment process has not yet been fully participatory and remains limited to a core group. The study also identifies several inhibiting factors, including weak social networks among local actors, non-participatory and unsustainable mapping of local potential, the absence of an inclusive shared vision, elite-dominated decision-making processes, limitations in collectively designing and implementing activities, and inadequate documentation and evaluation practices. The strategic analysis shows that community empowerment in tourism village development is positioned in Quadrant I (Strength–Opportunities), which requires the implementation of an aggressive–progressive strategy by optimizing the internal strengths of the community to capitalize on external opportunities in a sustainable manner. This strategy includes strengthening collective capacity, expanding collaborative networks, utilizing policy and technological support, and reinforcing local institutions to promote sustainable empowerment and enhance the competitiveness of the tourism village.